2007
DOI: 10.1518/001872007x230253
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Focus and Visual Recognition of Imagery Presented on Simultaneously Viewed Displays: Implications for Head-Mounted Displays

Abstract: For situations involving simultaneously viewed visual displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A third explanation for the differences between detection rates on the simulated vs. real HWD may lie in the differences between the focal plane of the target stimuli on the real HWD and the focal plane of the ongoing task. Winterbottom et al (2007) found that focal depth can affect the detectability of stimuli as well as visual comfort, and that the optimal focal depth should be the midpoint of the range of distances of potential stimuli. These distinctions, however, are for HWD imagery presented directly in the forward field of view, rather than peripherally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third explanation for the differences between detection rates on the simulated vs. real HWD may lie in the differences between the focal plane of the target stimuli on the real HWD and the focal plane of the ongoing task. Winterbottom et al (2007) found that focal depth can affect the detectability of stimuli as well as visual comfort, and that the optimal focal depth should be the midpoint of the range of distances of potential stimuli. These distinctions, however, are for HWD imagery presented directly in the forward field of view, rather than peripherally.…”
Section: Discussionmentioning
confidence: 99%
“…When people are engaged in mobile work, head worn displays (HWDs) can provide realtime access to information that might otherwise be unavailable or difficult to access. HWDs have been used to augment the worker's view with additional streams of hands-free information in a in a variety of high-tempo contexts such as manual assembly tasks (Büttner, Funk, Sand, & Röcker, 2016), controlling unmanned aircraft (Belenkii, Sverdrup, DiRuscio, & Taketomi, 2017), flight data for pilots (Winterbottom, Patterson, Pierce, Covas, & Winner, 2007;Winterbottom, Patterson, Pierce, & Taylor, 2006), infantry navigation data for soldiers (Glumm, Marshak, Branscome, McWesler, & Patton, 1998) as well as other augmented views of battlefields (Livingston et al, 2011). The intention is that the information provided by the HWD, often adapted to the location or context, will improve the worker's ability to carry out their tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice research indicates that binocular rivalry and eye dominance create difficulties for the observer in focusing on one or the other image at will. 6 The third barrier is perceptual. HWDs allow for a wide variety of display parameters, including focal distance, optical quality, degree of stereopsis, and fields of regard, all of which affect one's ability to perceive and extract information effectively.…”
Section: 1117/212009091735 Page 2/2mentioning
confidence: 99%
“…To some degree, HWDs have been associated with ill effects such as nausea and eyestrain. [4][5][6] In their review of thirty years of operational use of a monocular helmet-mounted display, Hiatt and collaborators report that pilots have experienced physical and visual symptoms such as headaches, blurred or distorted vision, and visual illusions that occur while using the display and in some cases persist for some time after use. 5 HWDs have also been found to affect attentional switching between the information displayed on the lens and that available only in the outside world.…”
mentioning
confidence: 99%
See 1 more Smart Citation